OC-057 A PH3 Randomised, Multicenter, Double-Blind, Placebo (PBO)-Controlled Study of Ustekinumab (UST) Maintenance Therapy in Moderate–Severe Crohn's Disease (CD) PTS: Results from IM-UNITI. (17th August 2016) - Sandborn, WJ; Feagan, BG; Gasink, C; Jacobstein, D; Gao, L-L; Johanns, J; Sands, B; Hanauer, S; Targan, S; Ghosh, S; de Villiers, W; Colombel, J-F; et al.
Abstract : Introduction: Single dose intravenous (IV) UST induced response and remission in CD pts refractory to TNF antagonists (UNITI-1) and failing conventional therapies (UNITI-2). The objective of this study (IM-UNITI) was to evaluate safety and efficacy of 2 subcutaneous (SC) UST regimens as maintenance therapy. Methods: Moderate-severe CD pts (n = 388 for primary study population) who achieved clinical response at Wk8 in 1 of 2 UST IV induction studies were randomly assigned to receive SC injections of PBO or UST 90 mg every 8 wks (q8w) or every 12 wks (q12w). The primary endpoint was clinical remission at Wk44. Results: A significantly greater proportion of pts in the UST grps were in clinical remission at Wk44 compared with PBO (53.1% & 48.8% in the q8w & q12w grps vs 35.9% PBO; p = 0.005 & p = 0.040, respectively). The treatment effect difference for q8w vs PBO (17.2%, [95%CI: 5.32%, 29.71%]) was numerically higher than the q12w grp (13.0%, [95%CI: 1.05%, 24.87%]. Primary, major, and other secondary endpoints in notable subsets are in Table 1 below. Similar proportions of pts with AEs were seen across treatment grps (81.7% & 80.3% for q8w & q12w vs 83.5% PBO). The proportions of pts with SAEs were 9.9%, 12.2%, and 15.0% among q8w, q12w, and PBO grps. Serious infections occurred in 2.3%, 5.3%, and 2.3% of pts in q8w, q12w, and PBO grps. Among the primary population, no deaths or major adverse cardiovascular events were reported, and 2 pts reported malignancies (1 basal cell carcinoma each in PBO and q8w grps). Conclusion: UST 90 mg q8w and q12w maintained clinical response and remission among pts with moderate-severe CD induced into clinical response with IV UST, with a favourable safety profile through Wk44. The q8w regimen more consistently demonstrated efficacy than the q12w regimen across the range of endpoints. Disclosure of Interest: W. Sandborn Grant/research support from: Receptos, Exact Sciences, Amgen, the American College of Gastroenterology, Broad Foundation, Prometheus Laboratories, AbbVie, Boehringer Ingelheim, Takeda, Atlantic Pharmaceuticals, Janssen, Bristol-Myers Squibb, Genentech, Pfizer, and Nutrition Science Partners, Conflict with: Personal fees from Receptos, Prometheus Laboratories, AbbVie, Boehringer Ingelheim, Takeda, Atlantic Pharmaceuticals, Janssen, Bristol-Myers Squibb, Genentech, Pfizer, Nutrition Science Partners, Kyowa Hakko Kirin, Millennium Pharmaceuticals, Celgene Cellular Therapeutics, Santarus, Salix Pharmaceuticals, Catabasis Pharmaceuticals, Vertex Pharmaceuticals, Warner Chilcott, Gilead Sciences, Cosmo Pharmaceuticals, Ferring Pharmaceuticals, Sigmoid Biotechnologies, Tillotts Pharma, Am Pharma BV, Dr. August Wolff, Avaxia Biologics, Zyngenia, Ironwood Pharmaceuticals, Index Pharmaceuticals, Nestle, Lexicon Pharmaceuticals, UCB Pharma, Orexigen, Luitpold Pharmaceuticals, Baxter Healthcare, Ferring Research Institute, Amgen, Novo Nordisk, Mesoblast Inc., Shire, Ardelyx Inc., Actavis, Seattle Genetics, MedImmune (AstraZeneca), Actogenix NV, Lipid Therapeutics Gmbh, Eisai, Qu Biologics, Toray Industries Inc., Teva Pharmaceuticals, Eli Lilly, Chiasma, TiGenix, Adherion Therapeutics, Immune Pharmaceuticals, Celgene, Arena Pharmaceuticals, Ambrx Inc., Akros Pharma, Vascular Biogenics, Theradiag, Forward Pharma, Regeneron, Galapagos, Seres Health, Ritter Pharmaceuticals, Theravance, Palatin, Biogen, and the University of Western Ontario (owner of Robarts Clinical Trials); non-financial support from Receptos, B. Feagan Grant/research support from: Abbott/AbbVie, Amgen, Astra Zeneca, Bristol-Myers Squibb (BMS), Janssen Biotech (Centocor), JnJ/Janssen, Roche/Genentech, Millennium, Pfizer, Receptos, Santarus, Sanofi, Tillotts, UCB Pharma, Consultant for: Abbott/AbbVie, Actogenix, Akros, Albireo Pharma, Amgen, Astra Zeneca, Avaxia Biologics Inc., Avir Pharma, Axcan, Baxter Healthcare Corp., Biogen Idec, Boehringer-Ingelheim, Bristol-Myers Squibb, Calypso Biotech, Celgene, Elan/Biogen, EnGene, Ferring Pharma, Roche/Genentech, GiCare Pharma, Gilead, Given Imaging Inc., GSK, Ironwood Pharma, Janssen Biotech (Centocor), JnJ/Janssen, Kyowa Kakko Kirin Co Ltd., Lexicon, Lilly, Lycera BioTech, Merck, Mesoblast Pharma, Millennium, Nektar, Nestles, Novonordisk, Pfizer, Prometheus Therapeutics and Diagnostics, Protagonist, Receptos, Salix Pharma, Serono, Shire, Sigmoid Pharma, Synergy Pharma Inc., Takeda, Teva Pharma, TiGenix, Tillotts, UCB Pharma, Vertex Pharma, VHsquared Ltd., Warner-Chilcott, Wyeth, Zealand, Zyngenia, Speaker bureau with: Abbott/AbbVie, JnJ/Janssen, Takeda, Warner-Chilcott, UCB Pharma, Conflict with: Patent holder; Member Scientific Advisory board, Abbott/AbbVie, Amgen, Astra Zeneca, Avaxia Biologics Inc., Bristol-Myers Squibb, Celgene, Centocor Inc., Elan/Biogen, Ferring, JnJ/Janssen, Merck, Nestles, Novartis, Novonordisk, Pfizer, Prometheus Laboratories, Protagonist, Salix Pharma, Takeda, Teva, TiGenix, Tillotts Pharma AG, UCB Pharma; Member, Board of Directors Officer – Robarts Clinical Trials Inc, C. Gasink Shareholder of: Janssen, Employee of: Janssen, D. Jacobstein Employee of: Janssen, L.-L. Gao Shareholder of: Janssen, Employee of: Janssen, J. Johanns Shareholder of: Janssen, Employee of: Janssen, B. Sands Grant/research support from: Janssen, Consultant for: Janssen, S. Hanauer Grant/research support from: Janssen, Consultant for: Janssen, Conflict with: Lecturer for Janssen, S. Targan Grant/research support from: Cedars-Sinai Medical Centre, Consultant for: Janssen, NuMedii, Inc., Conflict with: Advisory Board for Seaver Foundation; Scientific Advisory Board Member Symbiotix, S. Ghosh Grant/research support from: Abbvie, Conflict with: International Steering Committees: Janssen, Abbvie, Pfizer, Receptos, BMS, Aerpio; Advisory Committees: Takeda, Abbvie, Janssen, Pfizer, Allergan, W. de Villiers Conflict with: member of steering committee, active participant as investigator, J.-F. Colombel Consultant for: Pfizer, Takeda, Protagonist Therapies, Celgene, Genentech, Second Genome, Vertex, Amgen, Merck Sharp Dohme, Janssen, Nestle, AbbVie, Tigenix, Receptos, Conflict with: Speaker for AbbVie, Ferring, Shire, Takeda, S. Lee Grant/research support from: AbbVie Pharmaceuticals UCB Pharma Janssen Pharmaceuticals, Inc. Salix Pharmaceuticals Takeda Pharmaceuticals, Inc. Celgene Pharmaceuticals, Inc. Amgen Pharmaceuticals, Inc. Pfizer Pharmaceuticals, Inc., Consultant for: UCB Pharma Robarts Mesoblast Cornerstones Janssen Pharmaceuticals, Inc. Takeda Pharmaceuticals, Inc., L. Dieleman Grant/research support from: Canadian Institutes of Health and Research (CIHR) and Alberta Innovates Biosolutions, Consultant for: Janssen, Abbvie and Shire, S. Katz Grant/research support from: Abbott, Amgen, BMS, Centocor, Hutchison, Millennium, Pfizer, Receptos, Salix, Sanofi, Speaker bureau with: Abbvie, UCB, Actavis, P. Rutgeerts Grant/research support from: J&J, Merck, UCB, AbbVie, Consultant for: J&J, Merck, UCB, AbbVie, Millenium/Takeda, Genentech/Hoffman LaRoche, Medimmune/AstraZeneca/Amgen, Merck/Serono, Bristol-Myers Squibb, Robarts, Tillots Pharma, Conflict with: Lectures for J&J, Merck, AbbVie